Differential Modulation of Heat-Inducible Genes Across Diverse Genotypes and Molecular Cloning of a sHSP From Pearl Millet [Pennisetum glaucum (L.) R. Br.] - Mukesh Sankar, S.; Tara Satyavathi, C.; Barthakur, Sharmistha; Singh, Sumer Pal; Bharadwaj, C.; Soumya, S. L. (Frontiers in Plant Science, 2021)
The survival, biomass, and grain yield of most of the crops are negatively influenced by several environmental stresses. The present study was carried out by using transcript expression profiling for functionally clarifying the role of genes belonging to a small heat shock protein (sHSP) family in pearl millet under high-temperature stress. Transcript expression profiling of two high-temperature-responsive marker genes, Pgcp70 and PgHSF, along with physio-biochemical traits was considered to screen out the best contrasting genotypes among the eight different pearl millet inbred lines in the seedling stage. Transcript expression pattern suggested the existence of differential response among different genotypes upon heat stress in the form of accumulation of heat shock-responsive gene transcripts. Genotypes, such as WGI 126, TT-1, TT-6, and MS 841B, responded positively toward high-temperature stress for the transcript accumulation of both Pgcp70 and PgHSF and also indicated a better growth under heat stress. PPMI-69 showed the least responsiveness to transcript induction; moreover, it supports the membrane stability index (MSI) data for scoring thermotolerance, thereby suggesting the efficacy of transcript expression profiling as a molecular-based screening technique for the identification of thermotolerant genes and genotypes at particular crop growth stages. The contrasting genotypes, such as PPMI-69 (thermosusceptible) and WGI-126 and TT-1 (thermotolerant), are further utilized for the characterization of thermotolerance behavior of sHSP by cloning a PgHSP16.97 from the thermotolerant cv. WGI-126. In addition, the investigation was extended for the identification and characterization of 28 different HSP20 genes through a genome-wide search in the pearl millet genome and an understanding of their expression pattern using the RNA-sequencing (RNA-Seq) data set. The outcome of the present study indicated that transcript profiling can be a very useful technique for high-throughput screening of heat-tolerant genotypes in the seedling stage. Also, the identified PgHSP20s genes can provide further insights into the molecular regulation of pearl millet stress tolerance, thereby bridging them together to fight against the unpredicted nature of abiotic stress.